A Qualitative Study of an Intensive Filial Intervention Using Child–Parent Relationship Therapy (CPRT). (October 2015) - Socarras, Kristina; Smith-Adcock, Sondra; Shin, Sang Min
The purpose of this qualitative study was to hear from a group of African American parents who were living in poverty about their experience participating in a short-term, intensive child–parent relationship therapy intervention (CPRT). The parents who participated were recruited from a parent enrichment program for parents of preschoolers and were interviewed about the parent–child relationship before and after the group sessions. In addition, parents reported on barriers to utilizing counseling services related to their parenting needs. Following an intensive 4-week CPRT group intervention, the parents described their experiences about participating in the group sessions and how it impacted their parent–child relationship. Parents discussed changes in their perceptions of parenting, child's play, and CPRT group process. Implications are discussed.